2021
DOI: 10.11604/pamj.2021.38.244.26110
|View full text |Cite
|
Sign up to set email alerts
|

Sero-epidemiology of human coronaviruses in three rural communities in Ghana

Abstract: Introduction acute respiratory tract infections (ARIs) are responsible for significant proportions of illnesses and deaths annually. Most of ARIs are of viral etiology, with human coronaviruses (HCoVs) playing a key role. This study was conducted prior to the outbreak of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) to provide evidence about the sero-epidemiology of HCoVs in rural areas of Ghana. Methods this was a cross-sectional study conducted as part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In this study, we detected a generally moderate level of seroprevalence in 658 children under 15 years old for the three human coronaviruses (HCoV-229E, HCoV-NL63, HCoV-HKU1) and a high positive rate for HCoV-OC43. Although the seroprevalence of LPH-CoVs varies greatly by reason of different antigens used, methodologies adopted, population with distinct ages, and other demographic characteristics ( 25 27 ), the seroprevalence acquired from this cohort is somewhat in line with the normal range within children ( 28 30 ). Besides, the obvious maternal transient passive IgG antibodies response against LPH-CoVs was observed for infants within 3-months, which is consistent with the previous stratified studies ( 29 , 31 ).…”
Section: Discussionmentioning
confidence: 77%
“…In this study, we detected a generally moderate level of seroprevalence in 658 children under 15 years old for the three human coronaviruses (HCoV-229E, HCoV-NL63, HCoV-HKU1) and a high positive rate for HCoV-OC43. Although the seroprevalence of LPH-CoVs varies greatly by reason of different antigens used, methodologies adopted, population with distinct ages, and other demographic characteristics ( 25 27 ), the seroprevalence acquired from this cohort is somewhat in line with the normal range within children ( 28 30 ). Besides, the obvious maternal transient passive IgG antibodies response against LPH-CoVs was observed for infants within 3-months, which is consistent with the previous stratified studies ( 29 , 31 ).…”
Section: Discussionmentioning
confidence: 77%
“…In the current study, HCoVs were detected in 10.5% of the tested specimens, and distributed as follows: 57.2 % HCoV-229E, 33.3 % HCoV-NL63, and 9.5 % HCoV-HKU1. A study from Ghana (Owusu et al, 2021) also reported that HCoV-229E was the most isolated strain. The HCoV-OC43 virus was not detected in the tested specimens.…”
Section: Discussionmentioning
confidence: 85%
“…A recent hospital-based study of Ugandan patients with influenza-like illness demonstrated a high seroprevalence of HCoVs but used a nucleoprotein-based ELISA which could not distinguish between different species of HCoVs (Mulabbi et al, 2021). Molecular surveillance and seroprevalence studies in Kenya and Ghana, respectively, demonstrated the predominance of HCoV OC43 among HCoVs (Sipulwa et al, 2016;Owusu et al, 2021). These previous studies and our own underscore the potential public health significance of certain HCoVs, especially OC43, in Africa in the context of pre-existing cross-reactive IgA against SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%